2017
DOI: 10.1002/pchj.178
|View full text |Cite
|
Sign up to set email alerts
|

Time to learn: How chronotype impacts education

Abstract: A growing body of literature has linked chronotype and sleep to school performance. Chronotype is under the control of the circadian clock and refers to sleep timing and diurnal preferences. Chronotype changes with age and is latest during adolescence, giving rise to a mismatch between the (late) circadian clock and the (early) school clock. In general, evening (late) chronotypes obtain lower grades. School performance is influenced by many other factors, such as motivation, intelligence, and conscientiousness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 106 publications
(160 reference statements)
2
40
0
3
Order By: Relevance
“…The impact that research on chronotype has had on education and school policies is impressive. Starting in the 1990s, several studies have now shown how high-school students are constantly sleep deprived because of their late chronotype clashing with early school starting times and how this negatively influences their health and performance [103]. Some schools have, as a consequence, delayed their starting times.…”
Section: Discussionmentioning
confidence: 99%
“…The impact that research on chronotype has had on education and school policies is impressive. Starting in the 1990s, several studies have now shown how high-school students are constantly sleep deprived because of their late chronotype clashing with early school starting times and how this negatively influences their health and performance [103]. Some schools have, as a consequence, delayed their starting times.…”
Section: Discussionmentioning
confidence: 99%
“…The impact that research on chronotype has had on education and school policies is impressive. Starting in the 90s, several studies have shown how high-school students are constantly sleep deprived because of their late chronotype clashing with early school starting times and how this negatively influences their health and performance [95]. Some schools have, as a consequence, delayed their starting times.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of circadian preference and academic achievement showed that evening-orientated students were related to worse academic performance [46]. According to Zerbini et al, this effect is mediated by conscientiousness, learning/achieving motivation, mood, and alertness [47].In this context, the objective is to analyze, according to the gender of university students, possible differential patterns related to sleep. This study contributes to filling the gap in knowledge on the influence of students' gender on sleeping patterns.…”
mentioning
confidence: 99%
“…A recent meta-analysis of circadian preference and academic achievement showed that evening-orientated students were related to worse academic performance [46]. According to Zerbini et al, this effect is mediated by conscientiousness, learning/achieving motivation, mood, and alertness [47].…”
mentioning
confidence: 99%